The Effect of Teaching Reading in the Light of Linguistic Intelligence Skills in Developing the Skills of Expressive Writing of the Intermediate Stage Students in Iraq - الدليمي ثائر خلف; القاضي هيثم ممدوح (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The aim of the study was to investigate the effect of teaching reading in the light of linguistic intelligence skills in developing functional and creative writing skills among the second intermediate grade students in Iraq. In order to conduct the study; the researcher used the experimental method and he used a sample of the study consisted of (53) students, this group was divided randomly into two groups ,the experimental group with (26) students and the controlled group with (27) students. The study tool consisted of two writing topics, the first one is functional topic and the other is a creative one. The researcher ensured the validity and reliability of the test. The results of the study showed that teaching of reading in the light of linguistic intelligence skills had a statistically significant effect at the level of significance (0.05=α) in developing the two types of writing whether is functional or creative in favor of the experimental group. Accordingly; the researcher presented a number of recommendations such as: Encouraging Arabic language teachers to teach Arabic language materials, especially expressive writing, in light of linguistic intelligence skills.